Laparoscopic duodenojejunostomy requiring a side-to-side jejunojejunostomy in malignant stenosis of the gastrojejunal anastomosis in jejunal cancer: A case report. (2020) - Matsui, Yugo; Murakami, Teppei; Ishida, Satoshi; Mikami, Ryuichi; Matsuda, Shotaro; Tayama, Aoi; Sakata, Ryutaro; Harada, Takehisa; Takeo, Masahiko
Highlights: Laparoscopic duodenojejunostomy is a common intervention for the stricture of the distal duodenum. Not all patients respond to this intervention, and methods to treat them must be discussed. Opioid-induced bowel dysfunction caused fluids to accumulate in the jejunal loop in our case. Jejunojejunostomy was a solution to treat our patient. Abstract: Introduction: Laparoscopic duodenojejunostomy is a common surgical treatment for SMA syndrome. Although there are successful cases of laparoscopic duodenojejunostomies on malignant conditions, cancer patients with opioid-induced bowel dysfunction could struggle in maintaining an oral diet despite surgical treatment of the mechanical obstruction. Case presentation: A 66 year-old woman with a chemotherapy history of 18 months for Stage 4 jejunal cancer near the ligament of Treiz presented with vomiting and dehydration. She had a gastrojejunostomy constructed prior to the induction of chemotherapy. CT scan and endoscopic studies confirmed the stricture of this anastomosis due to tumor invasion. Laparoscopic duodenojejunostomy was performed, but tolerable food intake was not achieved, likely due to limited bowel movements caused by opioid use and tumor invasion of the celiac plexus. A side-to-side jejunojejunostomy was constructed, since accumulation of food in her jejunal loop was thought to be a significant cause of her limited food intake and vomiting. She was able to tolerate oral intake after the second intervention and was discharged home. Discussion: Successful cases of laparoscopic duodenojejunostomy in malignant strictures of the duodenum have been reported. In this case, the outcome was not so well due to limited bowel movements caused by opioid use. Literature review of laparoscopic duodenojejunostomy on SMA syndrome revealed some cases to be unsuccessful in enabling oral feeding or resolving nausea, and methods to treat such cases could be discussed further. Conclusion: Laparoscopic duodenojejunostomy is an option for malignant strictures of the duodenum, but a favorable outcome could not be achieved in our case. A side to side anastomosis of the jejunal loop and the efferent jejunum may help in improving the outcome.